Experimental study and numerical model of the seismic behavior of reinforced concrete beams in an artificial corrosion environment. (1st April 2022) - Zheng, Yue; Zheng, Shan-Suo; Yang, Lu; Dong, Li-Guo; Ruan, Sheng
Abstract: The corrosion of reinforcement materials induced by chloride attacks is the primary reason for the deterioration of the seismic performance of reinforced concrete (RC) structures. In this paper, 12 RC beams with different corrosion levels, shear span to depth ratios and stirrup ratios were subjected to accelerated corrosion tests in an artificial climate as well as quasistatic cyclic loading tests, and the corrosion form, failure process, bearing capacity, deformation capacity, energy dissipation capacity, stiffness and strength degradation of corroded RC beams were investigated. The results showed that the artificial climate corrosion method could simulate the uneven corrosion form of steel bars in a natural environment; the corrosion of steel bars would intensify the shear failure characteristics of specimens; the degradation rates of the bearing capacity and deformation capacity of corroded RC beams with different shear span to depth ratios and stirrup ratios are significantly different; and the degradation degree of bearing capacity of specimens with a high shear span to depth ratio is 3.58 times higher than that of specimens with a low shear span to depth ratio. Subsequently, a numerical modeling method for corroded RC beams based on SFI-MVLEM was proposed, empirical formulas for the stiffness coefficient of the corroded dowel were determined based on experimental data, and the bond-slip deformation was simulated by the infinitesimal algorithm and zero-length fiber section element. The proposed model was accepted to numerically simulate 12 corroded RC beams in this paper, and the average values of the bearing capacity error and energy consumption error of the simulation results were 10.07% and 13.09%, respectively, indicating that the proposed model had good accuracy and could be adopted to predict the residual seismic performance of corroded RC beams. Highlights: Artificial accelerated corrosion tests conducted on RC beam specimens. Investigation on seismic behavior of corroded RC beams with different design parameters. A set of numerical simulation analysis methods was proposed and verified to obtain the seismic responses of corroded RC beams.